Central Bank Digital Currencies: A Bibliometric Analysis - Pana, Elisabeta (Journal of Applied Business and Economics, 2021)
Rapid technological advances in electronic money and payment methods entice central banks to consider their role in an ever more digital world. Transformative changes to the financial and monetary system are met with an array of policy responses, including the issuance of central bank digital currencies. This paper examines the trends in the evolution of central bank digital currency literature and identifies the important features of the research area. A bibliometric analysis was used to analyze 77 journal articles on central bank digital currencies published from 2018 to 2020 in Scopus Database. Through performance, cocitation, and co-word analysis of the retrieved literature, we document the main journals, countries, authors, and emerging fields of research in central bank digital currencies.